1997
DOI: 10.1016/s0009-9236(97)90131-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of N-acetylation polymorphism and correlation with procainamide metabolism*

Abstract: We studied the genotypes of polymorphic N-acetyltransferase (NAT2) in 145 Japanese subjects by the polymerase chain reaction-restriction fragment length polymorphism method. The rapid-type NAT2*4 was expressed at a higher frequency (68.6%) than the slow-type genes with specific point mutations (NAT2*6A, 19.3%; NAT2*7B, 9.7%; NAT2*5B, 2.4%). The frequency of NAT2* genotypes consisted of 44% of a homozygote of NAT2*4, 49% of a heterozygote of NAT2*4 and mutant genes, and 7% of a combination of mutant genes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 32 publications
3
39
0
2
Order By: Relevance
“…On the other hand, in the Japanese population, the rapid-type NAT2*4 was present at a higher frequency (51.3%) than the slow-type (NAT2*5B, 1.6%, NAT2*6A, 26.1%, NAT2*6B, 2.2%, NAT2*7A, 1.2%, NAT2*7B, 10.1%) ( Table 2). These frequencies were similar to those reported by Okumura et al (1997) (NAT2*4, 68.6%, NAT2*6A, 19.3%, NAT2*7B, 9.7%, NAT2*5B, 2.4%). We also identified rare NAT2 variants, NAT2*6B and NAT2*7A, which had not been reported before in the Japanese population.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, in the Japanese population, the rapid-type NAT2*4 was present at a higher frequency (51.3%) than the slow-type (NAT2*5B, 1.6%, NAT2*6A, 26.1%, NAT2*6B, 2.2%, NAT2*7A, 1.2%, NAT2*7B, 10.1%) ( Table 2). These frequencies were similar to those reported by Okumura et al (1997) (NAT2*4, 68.6%, NAT2*6A, 19.3%, NAT2*7B, 9.7%, NAT2*5B, 2.4%). We also identified rare NAT2 variants, NAT2*6B and NAT2*7A, which had not been reported before in the Japanese population.…”
Section: Resultssupporting
confidence: 90%
“…INH, procainamide and some polycyclic amines). 14,[24][25][26][27] To date, a total of 17 mutant alleles have been found in the human NAT2 gene. 28,29) Parkin et al suggested the concordance between the NAT2 genotypes composed of the recently defined 14 mutant alleles and the acetylator phenotype of INH in patients with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…16) Five kinds of polymerase chain reaction (PCR) primers for NAT2 genotyping were synthesized by Rikaken Co. (Nagoya, Japan). 14) All other chemicals were of reagent grades and obtained commercially.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations